Feedstock for the petrochemical industry - Saon Ray; Amrita Goldar; Swati Saluja (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Petrochemicals play a vital role in the economy. The products of the industry are the building blocks in many industries including polymers, synthetic rubber, synthetic fibres, fibre intermediates and basic chemicals. The industry uses a variety of hydrocarbon feedstock such as different cuts of naphtha from refinery and natural gas (ethane and propane). Of the total ethylene capacity in the country, nearly 67 per cent is naphtha-based and 33 per cent is gas-based. This paper examines the feedstock scenario for petrochemicals in India in terms of availability, pricing, regulatory and fiscal issues. It also examines the feedstock scenario in the neighbouring region and assesses the competitive position of Indian petrochemical producer vis-à-vis producers in these countries. It provides an illustrative per unit cost of production for ethylene produced from both naphtha and ethane for India. Besides, it identifies the future challenges to the growth of the sector in India and suggests policy measures to strengthen India's competitive position.
Keywords: L65; D24; Q48; Q37; 330; natural gas price; naptha price; cost of production; import duty